(untitled) (Modern education and development, 2025)
The degree to which a language has maintained its original vocabulary, grammar, and structure without undergoing substantial influence or borrowing from other languages is commonly referred to as linguistic purity. Some languages are regarded as "pure" because of their historical continuity, geographic isolation, or intentional preservation attempts, even though no language is completely free from outside influence. Examples of languages known for their relative resistance to linguistic change or foreign borrowing are examined in this research, including Icelandic, Finnish, and Classical Hebrew. Because Icelandic is geographically and culturally isolated, it nevertheless has strong links to Old Norse. Being Uralic, Finnish has a distinct linguistic system with little Indo-European influence.